The Effect of Circle Passing Drill Training on Football Passing Skills at the Ps Club. Sakra in 2023 - Abdul Latif Hidayatullah (JOETAL: Journal of Education, Teaching and Learning, 2024)
The center of issue based on field discernments; there are some needs in terms of down and out passing accuracy. When they are playing passing can be easily cut off by the enemy as well as misplaced cleared out and right. Examine purposes the affect of cycle passing enter planning on soccer passing aptitudes at PS clubs Sakra in 2023. The explore technique utilized in this explore is arrange or arrange with an exploratory technique. Design of the research used one bunch pre test – post test arrange. So, the test utilized is PS soccer players at Sakra by totalling 20 players. The reviewing procedure livelihoods purposive analyzing. Ask around instrument the passing test focuses to degree kicking and holding the ball capacities. By having data examination, the t-count regard of X (passing) is 9,179 concurrent values between Y and so it can be concluded that seen from t-count > t-table 9,466 > 1,729). Therefore, there's an affect of cycle passing enter planning on skills passing football at the PS club Sakra in 2023.